comparison of calcification specificity in digital mammography using soft -copy display versus screen-film mammography - Diana Abbas Hamdy El-Sherif (2014)
Arabic Summary .
References (104-116).
Master in Medical Biophysics , Alexandria University :Medical Research Institute.
Keywords: Breast tumors